Connectedness in topology of intuitionistic fuzzy rough sets - Hazra, H; Samanta, S.K (Scientia magna, 2013)
After introducing the idea of fuzzy subsets by Lotfi Zadeh different variations/generalizations of fuzzy subsets were made by several authors. Zdzislaw I. Pawlak introduced the idea of rough sets. Later many authors dealt with the idea of fuzzy topology of different kinds of fuzzy sets. Here, Hazra and Samanta define Type-1 connectedness and Type-2 connectedness in topology of intuitionistic fuzzy rough sets and studied properties of two types of connectedness.